IS-26 1. Equine Oral Examination Using Oral Endoscope and 2. How to setup equine dentistry in your practice - Teerapol Chinkangsadarn (Hemera Zoa, 2018)
Developing of digital photography has brought veterinary services to another level of examination, disease diagnosis and client education. The use of oral endoscope with attached camera enhance the patient’s written dental record, thus it can also assist communication for case discussion among colleges or specialist for localize pathology, case follow up, treatment planning and practice marketing. It is not new technology but wildly use in veterinary practices. Unlike the flexible equipment used for internal endoscopy examinations for gastric ulceration, the dental scope is a rigid shaft called laparoscope with some degree of angle with led light source it can clearly visualize many small pathologies where conventional mirror visual are hard to detect.Equine dentistry once was neglect field of equine dentistry. For the past few years, almost every equine practice can perform routine dental examination with confidence where there some practices were specialist in equine dentistry with world recognize veterinary such USA, UK, Australia and SE Asia. It is also possible for small mixed/equine practice to have basic setup for equine dentistry with minimal investment and good quality of service is achieved. The basic setup starting from safe working area include mode of patient restrain which sedative protocol is recommended. Oral examination tools are consisting of full mouth speculum, dental mirror, pick, head support and dental chart. Training of veterinary skill is essential to perform correct examination technique, disease diagnosis and treatment planning. The post graduate training is part of current veterinary professional development, alike equine dentistry many institute or conference offer these training all over the world.    Equine dentistry once was neglect field of equine dentistry. For the past few years, almost every equine practice can perform routine dental examination with confidence where there some practices were specialist in equine dentistry with world recognize veterinary such USA, UK, Australia and SE Asia. It is also possible for small mixed/equine practice to have basic setup for equine dentistry with minimal investment and good quality of service is achieved. The basic setup starting from safe working area include mode of patient restrain which sedative protocol is recommended. Oral examination tools are consisting of full mouth speculum, dental mirror, pick, head support and dental chart. Training of veterinary skill is essential to perform correct examination technique, disease diagnosis and treatment planning. The post graduate training is part of current veterinary professional development, alike equine dentistry many institute or conference offer these training all over the world.